2020
DOI: 10.1111/cob.12373
|View full text |Cite
|
Sign up to set email alerts
|

Bariatric surgery in patients with psychiatric comorbidity: Significant weight loss and improvement of physical quality of life

Abstract: Summary Background Patients that have psychiatric comorbidity are thought to lose less weight than the general bariatric population and are therefore sometimes denied surgery. However, there is no scientific evidence for this assumption. The aim of this study is to evaluate the weight loss and health‐related quality of life (HRQoL) in patients with psychiatric disorders who undergo bariatric surgery and compare these patients with a general bariatric population. Method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Similarly, in the study of 199 patients who were observed for 2–3 years after bariatric surgery, pre-surgery psychiatric disorders were not related to weight change [ 5 ]. On the other hand, in study by Vermeer et al in bariatric patients, in whom 163 had preoperative diagnosis of psychiatric disease and 2362 had no such diagnosis, total weight loss 1 to 4 years after surgery was significantly lower in the psychiatric group [ 17 ]. However, the difference was rather small—about 5% lower weight loss in patients with diagnosis of mental disorders.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, in the study of 199 patients who were observed for 2–3 years after bariatric surgery, pre-surgery psychiatric disorders were not related to weight change [ 5 ]. On the other hand, in study by Vermeer et al in bariatric patients, in whom 163 had preoperative diagnosis of psychiatric disease and 2362 had no such diagnosis, total weight loss 1 to 4 years after surgery was significantly lower in the psychiatric group [ 17 ]. However, the difference was rather small—about 5% lower weight loss in patients with diagnosis of mental disorders.…”
Section: Discussionmentioning
confidence: 99%
“…The effectiveness of bariatric treatment is different in various groups and one of the determinants is the presence of mental disorders [ 5 ]. It may negatively affect eating behavior after bariatric surgery and patients’ adherence and as a consequence reduce the effectiveness of bariatric treatment [ 17 , 18 ]. Muller et al found that mental illness has a negative impact on weight loss in bariatric patients in a 4-year follow-up [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation